Solution NMR structure of CGL2373, a polyketide cyclase‐like protein from Corynebacterium glutamicum. Issue 1 (17th July 2019) - Cai, Cong; Nie, Yao; Gong, Yixuan; Li, Shuangli; Ramelot, Theresa A.; Kennedy, Michael A.; Yue, Xiali; Zhu, Jiang; Liu, Maili; Yang, Yunhuang
Abstract: Protein CGL2373 from Corynebacterium glutamicum was previously proposed to be a member of the polyketide_cyc2 family, based on amino‐acid sequence and secondary structure features derived from NMR chemical shift assignments. We report here the solution NMR structure of CGL2373, which contains three α‐helices and one antiparallel β‐sheet and adopts a helix‐grip fold. This structure shows moderate similarities to the representative polyketide cyclases, TcmN, WhiE, and ZhuI. Nevertheless, unlike the structures of these homologs, CGL2373 structure looks like a half‐open shell with a much larger pocket, and key residues in the representative polyketide cyclases for binding substrate and catalyzing aromatic ring formation are replaced with different residues in CGL2373. Also, the gene cluster where the CGL2373‐encoding gene is located in C. glutamicum contains additional genes encoding nucleoside diphosphate kinase, folylpolyglutamate synthase, and valine‐tRNA ligase, different from the typical gene cluster encoding polyketide cyclase in Streptomyces . Thus, although CGL2373 is structurally a polyketide cyclase‐like protein, the function of CGL2373 may differ from the known polyketide cyclases and needs to be further investigated. The solution structure of CGL2373 lays a foundation for in silico ligand screening and binding site identifying in future functional study.